PENGARUH PAJAK DAERAH, TRANSFER PEMERINTAH PUSAT DAN BELANJA MODAL TERHADAP PENDAPATAN ASLI DAERAH PEMERINTAH KABUPATEN/KOTA DI PROVINSI JAWA TENGAH TAHUN 2021 - Mohamad Makrus (JEM Jurnal Ekonomi dan Manajemen, 2022)
This study aims to analyze the effect of local taxes, central government transfers, and capital expenditures on local revenue (PAD) of district/city governments in Central Java province. These variables are designed in an equation model. The type of data used in this study is secondary data in the form of cross-section data of 33 regencies/cities in Central Java province, in the form of district/city APBD posture data in Central Java province, namely in the form of pure APBD data, APBD realization received by dynamic archival information systems (SIKD). The results of the study conclude that simultaneously and partially there is a significant effect of local taxes, central government transfers, and capital expenditures on local revenue (PAD) of district/city governments in Central Java province in 2021. Partially the three variables have a positive and significant influence on original district/city revenue in Central Java province in 2021.